Media animasi Powtoon: meningkatkan literasi digital guru - Marta, Rizkayeni; Giatman, Muhammad; Maksum, Hasan; Hikmah, Rezkiyana (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
This research aims to investigate the influence and effectiveness of using Powtoon animated media on teachers' digital literacy skills. The research approach is quantitative with an experimental design called one-group pretest-posttest design. the research population consists of all the English language teachers who are part of the MGMP in the Lima Puluh Kota District. The research sample comprises 19 teachers selected using random sampling techniques. The instrument used is a pretest-posttest exam, which will be analyzed using a paired sample t-test and N-gain score. The paired sample t-test resulted in a significance value (2-tailed) of 0.000, where the significance value (2-tailed) is less than the significance level of 0.05. The N-gain score test yielded a score of 0.4, which falls into the moderate category. This research concludes that Powtoon animated media has a significant influence and is effective in enhancing teachers' digital literacy skills. This research has a positive impact on the effectiveness of digital literacy among teachers in using Powtoon animation media.